Pengaruh Penggunaan Game Online Mobile Legend Terhadap Minat Belajar Siswa Kelas V SDN Cenang 03 - Lilis Widiyanti; Didik Tri Setiyoko; Muamar Muamar (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
The aim of the research is to find out whether there is an influence of playing the online game Mobile Legends on students' interest in learning in class V of SD Negeri Cenang 03. This type of research is quantitative. The data collection techniques used in this research include: questionnaires and documentation. The method used in this research is a quantitative survey. This research instrument uses 2 online game questionnaires and a learning interest questionnaire. Analysis of this research data uses the t test. The results obtained are the Mobile Legends online game on interest in learning. The results obtained through data analysis from the t test obtained a significant probability (sig) value of 0.031 < 0.05, which means it is smaller than 0.05. So it can be concluded that Ho is rejected and Ha is accepted, which means there is an influence of the mobile legends online game on interest in learning. Based on the results of the research above, it can be concluded that the mobile legends online game has an influence on interest in learning in class V of SD Negeri Cenang 03, Songgom District, Brebes Regency.